2018
DOI: 10.4103/jfcm.jfcm_82_17
|View full text |Cite
|
Sign up to set email alerts
|

Infant and young child feeding index and its association with nutritional status: A cross-sectional study of urban slums of Ahmedabad

Abstract: BACKGROUND:Infant and young child feeding (IYCF) practices are multidimensional and change rapidly in short intervals in the 1st year of life, asking for simultaneous assessment of various feeding dimensions in children of 6 months and older. Infant and Child Feeding Index (ICFI) is a composite index which measures complete feeding practices for infants and young children. The present study was conducted to assess IYCF practices for children aged 6–36 months in terms of ICFI and some sociodemographic factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…6 However it was much higher than the results in the studies of Mondal et al where it was 30.85% and Chaudhary et al where it was 15.7%. 24,25 This may be due to the high rates of illiteracy among the mothers in these studies as compared to the current study. It is much lower than that in the study conducted by Das et al where it was 83.3%.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…6 However it was much higher than the results in the studies of Mondal et al where it was 30.85% and Chaudhary et al where it was 15.7%. 24,25 This may be due to the high rates of illiteracy among the mothers in these studies as compared to the current study. It is much lower than that in the study conducted by Das et al where it was 83.3%.…”
Section: Discussionmentioning
confidence: 59%
“…It was less than the value found in the results of a study conducted by Chaudhary et al where it was 26.2% and Demilew et al where it was 23%. 25,32 The practice of bottle feeding is mostly a byproduct of an urban and affluent lifestyle since it is economically demanding. Since both these studies were conducted in urban areas, the similar lifestyle may be posited as an explanation.…”
Section: Discussionmentioning
confidence: 99%
“…6 The optimal use of nutritious food feeding is healthy for child growth and development. 7 Infectious diseases like diarrhea, pneumonia, and measles increase the risk of mortality among those children who are stunted, underweight and wasted children. 8,9 Practices of personal hygiene and sanitation are fundamental to avoid stunting among children and are useful for the growth and development of children (Rah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Child feeding index is a composite indicator which allows to measure IYCF practices in their entirety [50][51][52]. Reinbott et al reported that a child feeding index is superior to WHO IYCF indicators in explaining length-for-age Z-scores of young children [53].…”
mentioning
confidence: 99%